ET-04 MOLECULAR TARGETED THERAPY AGAINST (PRO)RENIN RECEPTOR FOR GLIOBLASTOMA. (16th December 2019) - Fujimori, Takeshi; Ogawa, Daisuke; Suzuki, Kenta; Kochi, Masaaki; Shibayama, Yuki; Okada, Masaki; Miyake, Keisuke; Nishiyama, Akira; Tamiya, Takashi
Abstract: INTRODUCTION: (Pro)renin receptor(PRR) is part of the Wnt receptor complex. Wnt/β-catenin signaling pathway (Wnt signaling) plays important role in pathogenesis and self-renewal of glioblastoma (GBM), or differentiation of glioma stem cell. We previously reported that PRR activate Wnt signaling, PRR expression correlated with malignancy of glioma, and treatment with PRR siRNA reduced the proliferative capacity. This time, we have developed monoclonal antibodies against PRR and examined their effects in GBM. MATERIAL AND METHODS: We used GBM cell line (U251MG and U87MG) and primary human glioma stem cell line (MGG23). Glioma stem-like cells were cultured and isolated by neurosphere method from U251MG and U87MG. PRR antibody was made targeting the extracellular domain of the PRR with rat lymph node method. WST-1 assay or MTT assay were performed to determine the cell proliferation. Apoptosis was examined by FITC labeled annexin V and propidium iodide with flow cytometry. We analyzed molecules of Wnt signaling and stem cell markers with qRT-PCR. RESULTS: We observed that PRR antibody significantly reduced cell proliferation, decreased sphere formation. Antibody suppressed cell adherent in stem-like cell. Flow cytometry showed that antibody induced apoptosis. Antibody inhibited Wnt signaling and stem cell markers. CONCLUSIONS: PRR antibody reduced cell proliferation and induced apoptosis through Wnt signaling. PRR antibody also suppressed stemness. Our results demonstrated that PRR was a potential target for future glioma therapy.